KORELASI DERAJAT KEMASAMAN TANAH DAN KANDUNGAN MERKURI TANAH BEKAS TAMBANG EMAS MELALUI APLIKASI BAHAN ORGANIK - Panji Romadhan; Gusmini Gusmini; Hermansah Hermansah (EnviroScienteae, 2022)
Ex-gold mining land is a soil which has poor chemical, physical, and biological properties so that its fertility is very low. Mercury (Hg) waste which is generated from the refining process of gold ore can pollute the environment. The purpose of this research was to determine the role of rice husk biochar, chicken manure, and sunflower plants in improving soil chemical properties and reducing Hg poisoning and to increase the production of sunflower as a source of renewables energy. This research used a completely randomized design method with 6 treatments and 4 replications. The treatments were consisted of a combination of rice husk biochar and chicken manure at a dose of 40 tons/ha equivalent to 100%. The results of this research should that the treatment of 100% chicken manure, pH value 6.28. Treatment of 100% rice husk biochar reduced mercury content in the soil up to 12.45 ppm.